Factors Influencing Entrepreneurial Interest In Agriculture (Case Study: Young Generation In Tinada District, Pakpak Bharat Regency) - Manik, Helmida (Sharia Agribusiness Journal, 2024)
ABSTRACTThis study aims to determine the factors that influence the entrepreneurial interest of the younger generation in the agricultural sector in Tinada District, Pakpak Bharat Regency. This type of research is quantitative in nature. The population of this research is the young generation in Tinada District with the sampling technique used, namely engineering proportional stratified random sampling. The questionnaire measurement scale uses a Likert scale which has been tested for validity and reliability. The results of the research show that the t test carried out proves: 1) the existence of a negative and significant influence of the family environment on entrepreneurial interest in the agricultural sector (tcount-6,411> ttable1.663 and significance 0.000 < 0.05), 2) there is a positive and significant influence of income expectations on entrepreneurial interest in agriculture (tcount7, 792 > ttable1.663 and a significance of 0.000 < 0.05), 3) there is a negative and significant influence of the level of education on interest in entrepreneurship in the agricultural sector (tcount-6,179 > ttable1.663 and significance 0.000 < 0.05). For the F test, this research shows that there is a positive and significant influence of family environment, income expectations, level of education on entrepreneurial interest in agriculture (Fcount 45,812 > Ftable 2.72 and significance 0.000 < 0.05). Meanwhile onadjusted r square shows that the joint results between the dependent variables in this study were 61.3% and the remaining 38.7% of the increase was influenced by other variables or factors that were not explained by this thesis research.Keywords: interests; entrepreneurship; generation; family; education   ABSTRAKPenelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi minat berwirausaha generasi muda di sektor pertanian di Kecamatan Tinada Kabupaten Pakpak Bharat. Jenis penelitian ini bersifat kuantitatif. Populasi penelitian ini adalah generasi muda di Kecamatan Tinada dengan teknik pengambilan sampel yang digunakan yaitu teknik proporsional stratified random sampling. Skala pengukuran kuesioner menggunakan skala likert yang telah teruji validitas dan reliabilitasnya. Hasil penelitian menunjukkan bahwa uji t yang dilakukan membuktikan: 1) adanya pengaruh negatif dan signifikan lingkungan keluarga terhadap minat berwirausaha di sektor pertanian (t hitung-6,411 > t tabel 1,663 dan signifikansi 0,000 < 0,05), 2) terdapat pengaruh positif dan signifikan harapan pendapatan terhadap minat berwirausaha di sektor pertanian (t hitung7,792 > t tabel 1,663 dan signifikansi 0,000 < 0,05), 3) terdapat pengaruh negatif dan signifikan tingkat pendidikan terhadap minat berwirausaha di sektor pertanian (t hitung-6,179 > t tabel 1,663 dan signifikansi 0,000 < 0,05). Untuk uji F, penelitian ini menunjukkan bahwa terdapat pengaruh positif dan signifikan antara lingkungan keluarga, harapan pendapatan, tingkat pendidikan terhadap minat berwirausaha di bidang pertanian (F hitung 45,812 > F tabel 2,72 dan signifikansi 0,000 < 0,05). Hasil gabungan antar variabel dependen dalam penelitian ini sebesar 61,3% dan sisanya sebesar 38,7% peningkatannya dipengaruhi oleh variabel atau faktor lain yang tidak dijelaskan oleh penelitian tesis ini.Kata Kunci: minat; kewirausahaan; generasi; keluarga; pendidikan